Information and communication technologies in tourism 2020 : proceedings of the International Conference in Surrey, United Kingdom, January 08-10, 2020 /: proceedings of the International Conference in Surrey, United Kingdom, January 08-10, 2020. (2020) - Unknown
No abstract available